The Effect of Financial Ratios on Growth Profit in Manufacturing Industry Sector Companies Listed on the Indonesia Stock Exchange - Fernanda Fadhli Fakhruddin; Titiek Ambarwati; Novita Ratna Satiti (Universitas Muhammadiyah Malang, 2021)
This research aims to find out the effect of financial ratio to profit growth on manufacturing industry companies or processing industries listed on the Indonesia Stock Exchange in 2016-2019. Purposive sampling techniques were obtained by 13 companies. The analysis used in this study is multiple linear regression analysis. The results in this study found that the current ratio partially positively affects profit growth, quick ratio partially positively and significantly affects profit growth, debt asset ratio partially negatively affects and significant on profit growth, debt equity ratio partially positively affects profit growth, total asset turnover partially positively affects profit growth. Working capital turnover partially positively affects but does not significant to profit growth, profit margin partially positively affects profit growth, retutn on asset partially positively affects profit growth. All free variables simultaneously have a significant effect on profit growth